1993
DOI: 10.1577/1548-8659(1993)122<0575:mubsrb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat Use by Stream-Resident Brown Trout: Bioenergetic Consequences

Abstract: Seasonal shifts in the microhabitats used by feeding brown trout Salmo trutta in a northern Spanish river were related to changes in habitat availability. At higher flows, mean water column velocities, focal velocities, and depths occupied by brown trout were greater and focal elevations above the substratum were less, but no changes in substratum use were detected. Cover use differed between dates, apparently according to the presence of suitable materials. In May, a lower proportion of the observed fish were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 45 publications
6
50
0
1
Order By: Relevance
“…Unfortunately, our results do not provide information about its discernment. From a univariate perspective, the mean velocity showed a wider suitable range in comparison with the optima in most of the studies in the Iberian Peninsula (0.0-0.4 m/s) (Ayllón et al, 2010;Rincon and Lobon-Cervia, 1993). However, our results were comparable with other authors (Hayes and Jowett, 1994) who did not attribute the highest suitability to very slow microhabitats, in contrast with other studies (Heggenes, 1996;Vismara et al, 2001) where habitat availability was more limited than in the present study.…”
Section: Model Transparency and Ecological Relevancesupporting
confidence: 61%
See 3 more Smart Citations
“…Unfortunately, our results do not provide information about its discernment. From a univariate perspective, the mean velocity showed a wider suitable range in comparison with the optima in most of the studies in the Iberian Peninsula (0.0-0.4 m/s) (Ayllón et al, 2010;Rincon and Lobon-Cervia, 1993). However, our results were comparable with other authors (Hayes and Jowett, 1994) who did not attribute the highest suitability to very slow microhabitats, in contrast with other studies (Heggenes, 1996;Vismara et al, 2001) where habitat availability was more limited than in the present study.…”
Section: Model Transparency and Ecological Relevancesupporting
confidence: 61%
“…Some studies on brown trout indicated such stable suitability for deep habitats (Bovee, 1978;Vismara et al, 2001). However, other studies indicated a decrease (Hayes and Jowett, 1994;Heggenes, 1996;Lambert and Hanson, 1989;Rincon and Lobon-Cervia, 1993) with optima approximately ranging from 0.5 to 1 m. This phenomenon could be a result of the modelling approach (Category II HSCs, after Bovee et al, 1998) or the absence of incoming drift (Hauer et al, 2012) rather than a negative direct effect of depth on the habitat suitability. Unfortunately, our results do not provide information about its discernment.…”
Section: Model Transparency and Ecological Relevancementioning
confidence: 98%
See 2 more Smart Citations
“…Substrate is generally considered very important for parr brown trout as a cover source (Heggenes, 1988b), with preference for coarser over finer substrates (Bachman, 1984;Huusko et al, 1997;Maki-Petays et al, 1997), and with fish size being positively correlated to grain size (Heggenes et al, 1999). Coarse substrate also reduces energy expenditure if fish are using surface tension velocity refuges (Heggenes and Saltveit, 1990;Rincon and Loboncervia, 1993) to act as direct cover from predators. It is known that the parr use the interstitial spaces between the substrate as refuge (Bachman, 1984;Bardonnet and Heland, 1994), and it can provide visual isolation from other juvenile trout (Shuler et al, 1994).…”
Section: Discussionmentioning
confidence: 99%